Assessing the feasibility of a weather index insurance for the semi-arid region of Brazil - Lavorato, Mateus Pereira (2020)
Weather index insurance (WII) has long been advertised as a viable alternative to overcome issues related to crop yield insurance products like information asymmetry and high transaction costs. WII products were firstly developed to assist climate-vulnerable farmers from developing countries where establishing a well-structured crop insurance market is expressively difficult due to the poor transport infrastructure and the prevalence of sparsely distributed small-scale farms. In Brazil, the semi-arid region stands out as the one that concentrates the ideal conditions for the implementation of a WII product since it houses thousands of climate-vulnerable family farmers. Seen this, the present study investigated the feasibility of a WII product for the Brazilian semi-arid region. A multidisciplinary approach based on meteorological, econometric and actuarial tools were employed, generating three distinct but complementary chapters. Firstly, it was shown that aridification is indeed a major threat to the livelihood of the population of the Brazilian semi-arid region. Secondly, it was identified that crop yield responses to weather conditions considerably vary in space and that an expressive portion of analyzed municipalities proved to have a low level of basis risk. Thirdly, a WII product was designed, priced and evaluated, proving to be effective in decreasing farmers’ downside risk. It is concluded, therefore, that it would be indeed feasible to establish a WII product in the semi-arid region of Brazil. Keywords: Feasibility. Weather Index Insurance. Brazil.